Changes in the Penetration Rate of Biosimilar Infliximab Within Japan Using a Japanese Claims Database - Matsumoto T; Tsuchiya T; Hirano T; Laurent T; Matsunaga K; Takata J (Dove Medical Press, 2021)
Tsugumi Matsumoto,1,2 Takanori Tsuchiya,3 Takahiro Hirano,4 Thomas Laurent,4 Kazuhisa Matsunaga,1 Jiro Takata1 1Faculty of Pharmaceutical Sciences, Fukuoka University, Fukuoka, Japan; 2Inflammation and Immunology Therapeutic Area Medical Affairs, Pfizer Japan Inc., Tokyo, Japan; 3Patient Impact Analysis, Outcome & Evidence, Corporate Affairs Health and Values, Pfizer Japan Inc., Tokyo, Japan; 4Clinical Study Support Inc., Nagoya, JapanCorrespondence: Jiro TakataFaculty of Pharmaceutical Sciences, Fukuoka University, 8-19-1, Nanakuma, Jonan-Ku, Fukuoka, 814-0180, JapanTel +81 92-871-6631Fax +81 92-871-663Email jtakata@fukuoka-u.ac.jpPurpose: Infliximab, which was approved in 2002, had its first biosimilar launched in 2014 across Japan. However, the penetration rate of this biosimilar remains unclear given the limited data regarding its current clinical use throughout Japan. This study was conducted to describe the current clinical characteristics of patients receiving infliximab and the penetration rate of the reference infliximab and/or biosimilar infliximab using a Japanese administrative claims database.Patients and Methods: This retrospective, descriptive study utilized the Japan Medical Data Vision database, a nationwide hospital-based database. Data on patients receiving infliximab recorded from April 2008 to March 2019 were extracted from the database. Patient characteristics of the reference and biosimilar infliximab groups and penetration rates according to fiscal year, target diseases diagnosis, and subsidy for intractable diseases were examined.Results: A total of 9735 patients were extracted for analysis, among whom 92% (n=8950) and 8% (n=785) received only reference infliximab and its biosimilar, respectively. Both groups exhibited similar clinical characteristics. The biosimilar penetration rate increased from 0.8% in 2014 to 22.5% in 2018, with overall penetration rates throughout the period according to diagnosis (with or without subsidy) being 14.4% (with, 4.1%; without, 16.4%), 4.7% (with, 3.7%; without, 10.6%), 5.7% (with, 4.5%; without, 13.5%), and 7.5% (with, 4.4%; without, 8.2%) for rheumatoid arthritis, Crohn’s disease, ulcerative colitis, and psoriasis, respectively.Conclusion: Biosimilar infliximab is prescribed for patients with similar characteristics to reference infliximab. Despite the increasing penetration rates according to target disease, they remain much lower among patients receiving subsidy for intractable disease than among those who do not.Keywords: intractable disease, biologics, TNF-α, rheumatoid arthritis, inflammatory bowel disease